Which therapeutic option for hepatitis C virus genotype 1?. (April 2014) - Brochot, Etienne; Helle, François; François, Catherine; Castelain, Sandrine; Capron, Dominique; Nguyen-Khac, Eric; Duverlie, Gilles
Abstract Objective. Sofosbuvir and simeprevir in combination with standard therapy are now available for the treatment of patients chronically infected with hepatitis C virus (HCV) genotype 1. With boceprevir and telaprevir, four treatment options are, therefore, now available to clinicians. Phase 3 studies conducted with simeprevir and sofosbuvir compared sustained virological response (SVR) data with those obtained with standard combination therapy and did not include a control arm. It is important to quantify the contribution of these molecules compared to the first direct antiviral agents available. Material and methods. For HCV genotype 1 patients, we performed a literature review and compared all SVR data from phase 3 randomized placebo-controlled trials conducted with these four molecules according to virological characteristics (genotype, viral load) and patient characteristics (IL28B polymorphism, stage of fibrosis). Results. Simeprevir and sofosbuvir provide a net gain in terms of SVR compared to boceprevir and telaprevir except in the case of telaprevir for treatment-naïve HCV genotype 1b patients. Sofosbuvir achieves higher SVR rates than simeprevir except for treatment-naïve IL28B CC patients and naïve HCV genotype 1b patient. Further, simeprevir moderately improve SVR rates compared to telaprevir in treatment-naïve patients with F3–F4 fibrosis and with HCV genotype 1a infection. Conclusion. Sofosbuvir and simeprevir greatly improve the virological response rate compared to first-generation protease inhibitors. All of these data may help in guiding the physician's treatment decisions, based on financial constraints and patient characteristics. These data can be easily updated with future treatment and demonstrate the contribution of new treatment regimens to achieve optimal SVR rates.